Pre-operative Assessment of Ablation Margins for Variable Blood Perfusion Metrics in a Magnetic Resonance Imaging Based Complex Breast Tumour Anatomy: Simulation Paradigms in Thermal Therapies. (January 2021) - Singh, Manpreet; Singh, Tulika; Soni, Sanjeev
Highlights: Extraction of three-dimensional patient-specific breast tumour anatomy from Dicom format Magnetic Resonance Images. Pre-clinical computational modelling and sparing healthy tissue characteristics within security rim of 10 mm. Confined fringe heating (Ablative Margin-3 mm) with thermal damage <5% in healthy tissue. Variable blood perfusion dynamics: moderate vs. high Temperature mapping (T≤95°C) in tumour core with thermal damage, (4 ≤ Ω ≤ 10). Abstract: Background and objectives : Image-guided medical interventions facilitates precise visualization at treatment site. The conformal prediction for sparing healthy tissue fringes precisely in the vicinity of irregular tumour anatomy remains clinically challenging. Pre-clinical image-based computational modelling is imperative as it helps in enhancement of treatment quality, augmenting clinical-decision making, while planning, targeting, controlling, monitoring and assessing treatment response with an effective risk assessment before the onset of treatment in clinical settings. In this study, the influence of heat deposition rate (SAR), exposure duration, and variable blood perfusion metrics for a patient-specific breast tumour is quantified considering the tumour margins thereby suggesting need of geometrically accurate models. Methods: A three-dimensional realistic model mimicking dimensions of a female breast, comprising 1.7 cm irregular tumour, was generated from patient specific two-dimensional DICOM format MRI images through image segmentation tools MIMICS 19.0® and 3-Matic 11.0® which is finally exported to COMSOL Multiphysics 5.2® as a volumetric mesh for finite element analysis. The Pennes bioheat transfer model and Arrhenius thermal damage model of cell-death are integrated to simulate a coupled biophysics problem. A comparative blood perfusion analysis is done to evaluate the response of tumour during heating considering thermal damage extent, including the tumour margins while sparing critical adjoining healthy tissues. Results: The evaluated thermal damage zones for 1 mm, 2 mm and 3 mm fringe heating region (beyond tumour boundary) reveals 0.09%, 0.21% and 0.34% thermal damage to the healthy tissue (which is <1%) and thus successful necrosis of the tumour. The iterative computational experiments suggests treatment margins < 5 mm are sufficient enough as heating beyond 3 mm fringe layer leads to higher damage surrounding the tumour approximately 1.5 times the tumour volume. Further, the heat-dosage requirements are 22% more for highly perfused tumour as compared to moderately perfused tumour with an approximate double time to ablate the whole tumour volume. Conclusions: Depending on the blood perfusion characteristics of a tumour, it is a trade-off between heat-dosage (SAR) and exposure/treatment duration to get desired thermal damage including the irregular tumour boundaries while taking into account, the margin of healthy tissue. The suggested patient-specific integrated multiphysics-model based on MRI-Images may be implemented for pre-treatment planning based on the tumour blood perfusion to evaluate the thermal ablation zone dimensions clinically and thereby avoiding the damage of off-target tissues. Thus, risks involving underestimation or overestimation of thermal coagulation zones may be minimised while preserving the surrounding normal breast parenchyma. Graphical abstract: This work illustrates patient-specific irregular breast tumour anatomy with thermal damage <5% in healthy tissue. This was achieved when confined fringe heating distance was restricted to 3 mm ablative margin region in comparison to surgical security rim of 10 mm. This excessive surgical resection margins suggests excessive healthy tissue damage near tumour boundaries which was found to be twice or thrice the tumour volume itself. These subjective and arbitrary estimates of excessive healthy tissue damage to avoid recurrence is more than desirable. Therefore, peripheral fringe heating zones were reduced to 5 mm region with achieved temperature of (T≤95°C) in tumour core, and thermal damage of (4 ≤ Ω ≤ 10). Protocol design for high perfusion case was demonstrated here in which desired thermal damage propagation time was restricted to 510 seconds to ensure safety of margins in healthy tissue that needs to be sacrificed. Here, Yellow bar and Blue bar shows 2 mm and 3mm fringe heating distance respectively. Previous experimental estimates suggests that thermal damage higher than Ω ≥ 10 doesn't holds any useful significance. When Ω ≥ 10, i.e. C( t ) ≥ e −Ω =5 × 10 −5 ; thermal damage process is fully developed and no information is added by continually accumulating the Ω integral. It is a quantitative measure to show remaining undamaged tissue constituents and mapped within a cross-section of MRI slice (axial plane) for true tumour shape possessing irregular nodes which were otherwise difficult to be treated surgically. For effective protocol design; heat propagation front once cover entire tumour zones, treatment end point was defined for prevailing perfusion in tumour. As per the design protocol, thermal damage penetration front in surrounding fringes must not exceed tumour volume while ensuring 99.6% of tumour damage. Thus, an interplay of temperature, thermal damage with variable blood perfusion dynamics was considered to optimize treatment time for a homogeneously perfused tissue. Image, graphical abstract